You & Your Aquarium - Mills, Dick (London Dorling Kindersley Ltd, 1987)
An updated edition of a reference title last published in 1987, which offers information and advice on the care of aquarium fishes, with details on feeding, health care, breeding and raising young fry, as well as advice on setting up tanks and descriptions and illustrations of over 120 fishes which are suitable for aquariums.
Including Illustration, Glossary, Appendices and Index
Keywords: Aquariums -- Aquarium fishes